Pemanfaatan Teknologi Dalam Peningkatan Penerimaan Zakat, Jumlah Muzaki, Dan Pengurangan Resiko Zakat - Basrowi Basrowi; Pertiwi Utami (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
The purpose of this study is to describe clearly the role of financial technology in increasing zakat receipts, facilitate management and distribution of zakat, increase the number of muzaki and reduce the risk of zakat management. The method used in this study is a qualitative descriptive method. Data taken from various secondary sources including the current literature derived from library materials and journals. Data were analyzed using a theme approach. The results of the analysis show that the use of financial technology is able to increase the number of muzaki, increase the receipt of zakat, reduce risk, which in turn can improve the welfare of muztahik and be able to reduce the number of muztahik to muzaki